Parry-Lord's Theory and Rāmāyaṇa of Vālmīki 1 - Krnic, Krešimir (Array, 2009)
The article deals with one part of Parry-Lord's theory of oral literature. Special attention is put towards analysis of formulaic and stereotyped expressions in the text of the Rā mā yaṇ a of Vā lmī ki. The quantitative analysis of the formulas in the text have shown that the theory as a starting point and a principle is correct and very useful in deciding oral or written nature of the given text. But, at the other hand, it has also shown that the percentage of expected formulaic expressions in an oral text is much less then the founders of the theory have proposed.